La aplicación de las nuevas tecnologías de la información y la comunicación (ntic´s) en la asignatura de marketing relacional en los estudiantes de la carrera de ingeniería comercial de la universidad técnica de cotopaxi, en el período 2014-2015 - Soto Cuchiparte, Marcos (2015)
This research came up by the necessity of uses of new technologies of the information and communication (NTIC’s) in the educative subject process of the Commercial Engineer Carrier of the Cotopaxi Technical University, the objective is to create the user manual of Molecule Free Software MFS. for using of marketing students to improve in the teaching – learning process where students can put into practice the theoretical knowledge, and thus enhance the teachers and students' relationships. This research was used the methodology that is formed by two kinds of research such us deductive an inductive, sadistic technics and instruments through that conclude that is necessary….